Improving nutrient management practices in agriculture: The role of risk‐based beliefs in understanding farmers' attitudes toward taking additional action. Issue 8 (21st August 2014) - Wilson, Robyn S.; Howard, Gregory; Burnett, Elizabeth A.
Abstract A recent increase in the amount of dissolved reactive phosphorus (DRP) entering the western Lake Erie basin is likely due to increased spring storm events in combination with issues related to fertilizer application and timing. These factors in combination with warmer lake temperatures have amplified the spread of toxic algal blooms. We assessed the attitudes of farmers in northwest Ohio toward taking at least one additional action to reduce nutrient loss on their farm. Specifically, we (1) identified to what extent farm and farmer characteristics (e.g., age, gross farm sales) as well as risk‐based beliefs (e.g., efficacy, risk perception) influenced attitudes, and (2) assessed how these characteristics and beliefs differ in their predictive ability based on unobservable latent classes of farmers. Risk perception, or a belief that negative impacts to profit and water quality from nutrient loss were likely, was the most consistent predictor of farmer attitudes. Response efficacy, or a belief that taking action on one's farm made a difference, was found to significantly influence attitudes, although this belief was particularly salient for the minority class of farmers who were older and more motivated by profit. Communication efforts should focus on the negative impacts of nutrient loss to both the farm (i.e., profit) and the natural environment (i.e., water quality) to raise individual perceived risk among the majority, while the minority need higher perceived efficacy or more specific information about the economic effectiveness of particular recommended practices.